Sex & social justice - Nussbaum, Martha C. (Martha Craven), 1947- (Oxford University Press, 1999)
Growing out of Nussbaum's years of work with an international development agency connected with the United Nations, this collection charts a feminism that is deeply concerned with the urgent needs of women who live in hunger and illiteracy, or under unequal legal systems. Offering an internationalism informed by development economics and empirical detail, many essays take their start from the experiences of women in developing countries. Nussbaum argues for a universal account of human capacity and need, while emphasizing the essential role of knowledge of local circumstance. Further chapters take on the pursuit of social justice in the sexual sphere, exploring the issue of equal rights for lesbians and gay men.